Al-Qur’an dalam Sejarah Penafsiran Indonesia: Analisis-Deskriptif Beberapa Tafsir di Indonesia - siti fahimah (STIU Al-Mujtama Pamekasan, 2019)
Abstract: The history of interpretation in Indonesia is no less important and rampant with a history of interpretation in the Arab world. Interpretation in Indonesia began in the early 17th century up to now with various genres, the rise of interpretations produced by Indonesians indicates that the Koran wants to be understood in the context of Indonesia with a variety of languages ​​and approaches as well as the writer's back. The number and categorization are very many, some use thematic methods and approaches there are also those who understand the Qur'an as a whole the Koran by adopting the classical Arabic exegetical methods and methods. In this paper the author has succeeded in discovering and describing 22 books categorized as interpretations produced by Indonesians in various patterns and methods, not to the possibility that there are still many interpretations in Indonesia that have not yet been touched. Indonesia is presented in the form of interpretation. As for the interpretation of interpretations as outlined in this paper just to describe it, around the figure of the interpreter in general, then the model and style. Keywords: Indonesian interpretation, history, al-Quran